One step synthesis of 4,6,8-Trimethoxyazulenes: as building block for 2-functionalized azulenes - Wunsch, Jonas; Sommer, Hendrick M.; Kohl, Senta J.; Maier, Rouven; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2025)
Here we present a simple gold-catalyzed one-pot reaction of easily available diarylbutadiynes, with trimethoxybenzene as solvent and reactant to synthesize 4,6,8-trimethoxyazulenes. The methoxy substituents, which render the azulene very electron-rich, enable a change of azulenes typical regioselectivity for electrophilic substitutions, which enables facile electrophilic 2-substitution with iodine, bromine, chlorine, selenium or sulfur. Especially the 2-haloazulenes which can usually only be obtained through lengthy multistep syntheses are valuable building blocks for the synthesis of 2-substituted azulene derivatives.
Veröffentlicht: 07. Januar 2025
Gesehen am 07.04.2025